IJCM_169A: Correlation of sonographic renal dimensions with anthropometric measurements among individuals without renal disorders - Jagadish Swathi; Kalaria Keshavi M; Bhat Nagaraj; Harshita M R; Shetty Monisha; Holla Ramesh; Mithra Prasanna; Kumar Nithin; Motappa Rohith; Rao Mithun (Indian Journal of Community Medicine, 2024)
Background: Normal kidney dimensions are suggestive of normal kidney function. Degree of kidney function has a positive correlation with ultrasonic renal measurements. Co-morbid conditions affect the renal size. Therefore it becomes necessary to establish normal values of kidney dimensions for the diagnosis, prognosis and also as an early indication of renal diseases in order to prevent them. Objectives: To study the renal dimensions and association with socio- demographic conditions among the outpatient attendees in the study hospital. Methodology: This was a descriptive cross-sectional study done among the attendees of KMC Hospitals, Mangalore. Data extraction sheet included the socio-demographic details, Anthropometric measurements, personal history, history of comorbidities and sonographic dimensions of Kidney and laboratory findings of Renal Function Test. Data was entered and analyzed by using statistical software Statistical Package for Social Sciences (SPSS) Version 29.0. Results: Out of 194 participants, 118(60.8%) were males. The difference between corresponding kidney lengths of males and females is found to be statistically significant. The length and anteroposterior dimension of left kidney is greater than right kidney and the difference is statistically significant. When the kidney lengths and the heights of the individual were correlated a positive correlation was obtained, (0.278) in case of right kidney and (0.245) in case of left kidney. Conclusion: Kidney length had positive correlation with height and BMI. Female kidney length was significantly smaller than the male kidney length. There was significant variation between right and left kidney lengths.